An uninterpreted spatial version of the trust game: Evidence of reciprocity without suggestive words, evidence of iterated dominance self-taught - Talbot Page; Louis Putterman (Brown University, Department of Economics, 2012)
In this working paper we report on two trust games: a BDM-like game which is interpreted through its use of the possibly suggestive words show up fee, sends, tripled, send back; and an uninterpreted spatial game that does not use these words suggestive or not. In the spatial game we found a considerable amount of reciprocity, which implies the words are not necessary for reciprocity. For further comparison we designed the two games to have a correspondence relation (the relation extends to the original BDM trust game). We focused on two variables - interpreted or uninterpreted and spatial or word-based. We also designed constants which were identical or near identical in the two games. We did this to reduce confounding in statistical comparisons. We found the frequency of reciprocity in the spatial game, without the suggestive words, was about the same as the frequency of reciprocity in the BDM-like game, with the suggestive words. We found iterated dominance in the spatial game was 5.5 times higher than in the BDM-like game. And we found sending the full endowment was significantly more frequent in the BDM-like game than in the spatial game.
Keywords: 330